2008
DOI: 10.1111/j.1365-2982.2008.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the oesophageal transition zone in the presence of chronic bolus retention: studies using concurrent high resolution manometry and digital fluoroscopy

Abstract: Distinct contraction waves (CWs) exist above and below the transition zone (TZ) between the striated and smooth muscle oesophagus. We hypothesize that bolus transport is impaired in patients with abnormal spatio-temporal coordination and/or contractile pressure in the TZ. Concurrent high resolution manometry and digital fluoroscopy were performed in healthy subjects and patients with reflux oesophagitis; a condition associated with ineffective oesophageal contractility and clearance. A detailed analysis of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 29 publications
2
69
0
1
Order By: Relevance
“…The transition between them is identified as the transition zone where the proximal contraction wave originating in the striated esophagus terminates and below which a distal contraction wave simultaneously forms and propagates into the distal smooth muscle esophagus (Ghosh et al, 2006). Ghosh et al (2008) reported that weak mid esophageal contractions at the proximal smooth-muscle segment appear to be the cause of impaired clearance function. Martinek et al (2008) reported no difference between NERD and mild to moderate erosive esophagitis in terms of motor abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The transition between them is identified as the transition zone where the proximal contraction wave originating in the striated esophagus terminates and below which a distal contraction wave simultaneously forms and propagates into the distal smooth muscle esophagus (Ghosh et al, 2006). Ghosh et al (2008) reported that weak mid esophageal contractions at the proximal smooth-muscle segment appear to be the cause of impaired clearance function. Martinek et al (2008) reported no difference between NERD and mild to moderate erosive esophagitis in terms of motor abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, HRM has been used to characterize this region, and parameters such as the proximal contractile integral (PCI, by analogy with the DCI) can now quantify the profile of this area. 26 Although an isolated defect in this region is a rare cause of dysphagia, it may represent a distinct motility disorder.…”
Section: Importance Of Transitional Zonementioning
confidence: 99%
“…[4,5]. Die hochauflösende Manometrie ermöglicht in einer kontinuierlichen Darstellung der Druckmesswerte ("spatiotemporal plot") eine objektive Darstellung der physikalischen Druckgradienten für einen Bolustransport vom Pharynx in den Magen (.…”
Section: Oropharyngeale Dysphagieunclassified